DNA methylation of the cancer-related genes F2RL3 and AHRR is associated with occupational exposure to polycyclic aromatic hydrocarbons. (2nd May 2018) - Alhamdow, Ayman; Lindh, Christian; Hagberg, Jessika; Graff, Pål; Westberg, Håkan; Krais, Annette M; Albin, Maria; Gustavsson, Per; Tinnerberg, Håkan; Broberg, Karin
Abstract : This study showed that chimney sweeps and creosote workers had lower DNA methylation of F2RL3 and AHRR, which is a risk factor for lung cancer. PAH exposure from soot and creosote oil likely play a role in this epigenetic modification. Abstract: Some polycyclic aromatic hydrocarbons (PAH) are known carcinogens and workplace PAH exposure may increase the risk of cancer. Monitoring early cancer-related changes can indicate whether the exposure is carcinogenic. Here, we enrolled 151 chimney sweeps, 152 controls and 19 creosote-exposed male workers from Sweden. We measured urinary PAH metabolites using LC/MS/MS, the cancer-related markers telomere length (TL) and mitochondrial DNA copy number (mtDNAcn) using qPCR, and DNA methylation of lung cancer-related genes F2RL3 and AHRR using pyrosequencing. The median 1-hydroxypyrene (PAH metabolite) concentrations were highest in creosote-exposed workers (8.0 μg/g creatinine) followed by chimney sweeps (0.34 μg/g creatinine) and controls (0.05 μg/g creatinine). TL and mtDNAcn did not differ between study groups. Chimney sweeps and creosote-exposed workers had significantly lower methylation of AHRR CpG site cg05575921 (88.1 and 84.9%, respectively) than controls (90%). Creosote-exposed workers (73.3%), but not chimney sweeps (76.6%) had lower methylation of F2RL3 cg03636183 than controls (76.7%). Linear regression analyses showed that chimney sweeps had lower AHRR cg05575921 methylation ( B = –2.04; P < 0.057, adjusted for smoking and age) and lower average AHRR methylation ( B = –2.05; P < 0.035), and non-smoking chimney sweeps had lower average F2RL3 methylation ( B = –0.81; P < 0.042, adjusted for age) compared with controls. These cancer-related markers were not associated with urinary concentrations of PAH metabolites. In conclusion, although we found no associations with PAH metabolites in urine (short-term exposure), our results suggest dose–response relationship between PAH exposure and DNA hypomethylation of lung cancer-related loci. These findings indicate that further protective measures should be taken to reduce PAH exposure.